Ut pictura poesis - Širca, Alen Albin (Ars et humanitas, 2011)
This article discusses the concept of intermediality, comparing traditional visual poetry and contemporary digital poetry. It shows that today's somewhat fashionable concept of intermediality can actually be traced in the transposition of the classic concept of intertextuality from philosophical discourse, especially as developed by Barthes and Kristeva, to the domain of mediological discourse. The article briefly summarizes the tradition of visual poetry from antiquity to modernism, emphasizing its structure as basically concrete; that is, it implies a material and medial component of language or writing (écriture). This structure calls attention to its self-referential and referential aspect. The digital poetry that continues the line of development of concrete poetry, as it appeared in the 1950s and 1960s, belongs to a broader area of new media poetry that includes any experimental poetry that uses the "new" media. The problematic concept of intermediality can best be explored in a digital environment such as the holographic poetry (or holopoetry) of the noted and versatile contemporary Brazilian artist Eduardo Kac. Kac's holopoetry is a special space-time event in the context of the holographic projection of the text in order to display its multilinearity, which primarily means breaking with the linearity of classic poetry printed in a book. Based on an examination of Kac's holopoem "Havoc" from 1992 (in this example, the poem's graphic integrity is temporarily lost), the paper challenges the simplistic deconstructivist interpretation that is applied to Kac's poems and often to digital poetry in general: namely, that these poetic events can most persuasively be seen as figures for the unattainability of "pure" presence/absence, materiality/ immateriality, reality/virtuality, and so on. The author argues that the "polluted" reading as a reading against metaphysics and tradition in the case of new-media poetry is unconvincing because the visually evident and naive representation of a (would-be) Derridaean différance is nothing more and nothing less than the Baudrillardean simulacrum: an imaginary representation of the unreal. The author concludes by suggesting that the basic intermedial problems of contemporary digital poetry remain the same as in traditional visual poetry; that is, that they are only reproduced in the new media environment. Their new "materiality" and the extensive possibilities of technical manipulations that they offer should not deceive us that they ipso facto imply completely new ontological dimensions.
Keywords: Kac, Eduardo, 1962-; literature and electronic media; visual poetry; literatura; literature; digital poetry; elektronski mediji; holopoetry; vizualno pesništvo; cyberspace; digitalna poezija; holografska poezija; intertextuality; intermediality; kiberprostor; medbesedilnost; intermedialnost